2022
DOI: 10.1038/s43705-022-00111-w
|View full text |Cite
|
Sign up to set email alerts
|

Phage-encoded ribosomal protein S21 expression is linked to late-stage phage replication

Abstract: The ribosomal protein S21 (bS21) gene has been detected in diverse viruses with a large range of genome sizes, yet its in situ expression and potential significance have not been investigated. Here, we report five closely related clades of bacteriophages (phages) represented by 47 genomes (8 curated to completion and up to 331 kbp in length) that encode a bS21 gene. The bS21 gene is on the reverse strand within a conserved region that encodes the large terminase, major capsid protein, prohead protease, portal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Approximately 7.7% of phage scaffolds were circularized and thus likely represent complete genome sequences (Table S9). We merged these newly-reported phage scaffolds with those from our previous studies of the same environment [26,27] and subjected the total set of ∼800 non-redundant phage scaffolds to a network analysis based on protein content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 7.7% of phage scaffolds were circularized and thus likely represent complete genome sequences (Table S9). We merged these newly-reported phage scaffolds with those from our previous studies of the same environment [26,27] and subjected the total set of ∼800 non-redundant phage scaffolds to a network analysis based on protein content.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 7.7% of phage scaffolds were circularized and thus likely represent complete genome sequences (Table S9). We merged these newly-reported phage scaffolds with those from our previous studies of the same environment [26,27] and subjected the total set of ~800 non-redundant phage scaffolds to a network analysis based on protein content. This analysis revealed that many phages from Lac Pavin fall into broad clusters with known phages from diverse environments, suggesting they are part of well-sampled clades defined by protein content ("mixed" clusters, Fig.…”
Section: Diversity and Characteristics Of Recovered Phage Genomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that bS21 might modulate translation for a subset of mRNAs is further supported by the recent discovery that bS21 is encoded by thousands of sequenced bacteriophage genomes and is one of the most commonly encoded phage ribosomal proteins ( 52 , 53 ). Transcripts encoding bS21 have been detected in metatranscriptomic samples along with transcripts for late-stage replication proteins ( 54 ) and at least one phage-encoded bS21 can be incorporated into E. coli ribosomes ( 52 ). All of this raises the possibility that the incorporation of a viral bS21 into the host ribosome may co-opt the translation machinery in favor of viral proteins and replication.…”
Section: Discussionmentioning
confidence: 99%